The Role of Banking in Micro, Small and Medium Enterprises (Study of BPRS Saruma Financing in the Agriculture and Fisheries Sector) - Abas, Sofyan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Micro, Small and Medium Enterprises (MSMEs) as pillars supporting the Indonesian economy need special attention, including banking financial institutions, because the contribution of the MSME sector to the national economy is quite large. Sharia People's Financing Bank (BPRS) Saruma Sejahtera Halmahera South Regency has carried out all the systems that have been established in accordance with the mandate of law number 21 of 2008 concerning Islamic banking, namely providing financing based on contracts that do not conflict with sharia principles, namely profit sharing that does not harm the party customers include Micro, Small and Medium Enterprises (MSMEs) so that they can run their businesses. BPRS Saruma Sejahtera Halmahera Selatan with a Financial intermediation function can encourage economic activity, because it can lead to a flow of funds from parties who are not productive to those who are productive in managing funds. Furthermore, this will help the economy to become more efficient and dynamic. This research is a qualitative research, it is hoped that it will be able to find out how far the alignment of Islamic banking is in the real sector, namely Micro, Small and Medium Enterprises (MSMEs). The results of this journal research are to find out the basic procedures for analyzing financing or credit from the Saruma Sejahtera Halmahera Selatan Syariah People's Financing Bank to MSME actors, both businesses in the agricultural and fisheries sectors.